Management Of Class II Malocclusion In A Post-pubertal Patient with A Modified Fixed Twin Block and Fixed Orthodontic Therapy: A Case Report - M, Dharini; M, Hemanth; Shaji, Sanjana; Gaonkar, Shivaprasad; BR, Kavya; Pramod, Shyama (Journal of Neonatal Surgery, 2025)
Functional appliances have long been employed in the management of skeletal Class II malocclusions, with their primary objective being to stimulate mandibular growth by enhancing growth activity at the condylar cartilage. Among the myofunctional appliances, the Twin Block appliance is one of the most widely used due to its effectiveness and patient compliance. The aim of this paper is to present a case report of mandibular deficiency treatment with modified Fixed Twin Block appliance in a female patient whose sexual maturation (one year after menarche) and cervical vertebral maturation stage assessment indicated the end of peak pubertal growth . Diagnosis revealed an Angle’s Class II malocclusion with an orthognathic maxilla, retrognathic mandible, horizontal growth pattern, recessive chin, and a convex facial profile. Phase I treatment was carried out using a modified fixed twin block appliance, which improved mandibular growth, facial balance. This was followed by a support phase with a Rick-A-nator and subsequently Phase II fixed mechanotherapy using 0.022 in MBT prescription. Post- treatment, the patient exhibited improved skeletal relationship and a harmonious soft tissue profile and Class I relationship with normal overjet and overbite was achieved.